Bryoflora of tbe City of Salamanca (Spain) - Benito Ayuso, J.; Rupidera Giraldo, José Luis; Elías Rivas, María Jesús (Botanica Complutensis, 1995)
Ayuso. J. B. ELÍAS RIvAS, M. J. & RUPIOBRA GIRALDo, 1. L. ¡995. Brioflora de la Ciudad de Salamanca. Boí. Complatensts 20: 45-53. Thirty eight bryophytes (37 mosses and ¡ liverwort) are reponed from the city of Salamanca (Spain). 6 are newly for the province.